THE EFFECT OF THE GOOGLE CLASSROOM APPLICATION ON THE STUDENTS’ WRITING SKILLS IN SMA SWASTA GAJAH MADA MEDAN DURING COVID-19 PANDEMIC - Irma Khoirot Daulay; Agnes Charismah Iman Putri Zendrato; Jeffry Jeffry; Neslita Elisabeth Manik; Priska Simamora (Universitas Islam Sumatera Utara, 2021)
The research aims to determine the effectiveness of applying the Google Classroom Application on the students' Writing Skills from grade X1 of SMA Swasta Gajah Mada Medan. The research applied the quantitative method with experimental design. The data were analyzed using the mathematics system related to the methods applied in the research. According to the research findings, it is concluded that Applying Google Classroom Application potentially gives more effectiveness in teaching writing skills to the students. After the post-test is done, the mean score of applying Google Classroom Application is 85.65. The standard deviation is 7.353, and the number of students is 26. The mean by applying conventional strategy is 62.00, the standard deviation is 3.943, and the number of students is 24. From the research result, the researchers found that the mean score of the experimental group students was improved by 17.10. In the controlled group, the mean score of the students was improved by 9.75. After the post-test by applying Google Classroom Application to the students is undertaken, the normality test result is 0.465. After a post-test to the students by applying the conventional teaching method in the controlled group is given, the normality test result is 0.243. The research finding explained that the Google Classroom Application successfully improved the students' writing skills, especially at SMA Swasta Gajah Mada Medan during the Covid-19 pandemic.